Mewujudkan Kemandirian Ekonomi Keluarga melalui Pelatihan Pengelolaan Keuangan bagi Penerima PKH di Kecamatan Muara Bangkahulu Kota Bengkulu - Apriyanti, Cikit; Ridwan, Mochamad; Yusnida; Kumara, Bima Prasetya; Octarrum, Devina (UNIB Press, 2025)
This community service activity aims to improve literacy and household financial management skills for recipients of the Family Hope Program (PKH) in Muara Bangkahulu District, Bengkulu City. Through educational activities and hands-on practice, participants are expected to be able to manage aid funds more productively in order to achieve family economic independence. The implementation methods included socialization, material delivery, interactive discussions, case studies, as well as financial recording and household budget preparation exercises. The results of the activity showed an increase in participants' understanding of the importance of financial planning, discipline in recording cash flow, and the ability to allocate assistance funds for productive activities. This activity also motivated participants to start saving and developing small businesses